Monopolistic competition theory origins, results, and implications - Keppler, Jan (Johns Hopkins Univ. Press, 1994)
Economists such as Piero Sraffa, Joan Robinson, and Edward Chamberlin thus began to develop monopolistic competition theory in order to raise theory's empirical relevance as well as its analytical sharpness